2018
DOI: 10.1039/c7cp06139k
|View full text |Cite
|
Sign up to set email alerts
|

Robust light harvesting by a noisy antenna

Abstract: Ultrafast bulk and single-molecule spectroscopy experiments described by a single theoretical model show how protein fluctuations influence photosynthetic light harvesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…81 The diversity of pigment types and the controlled interactions between them and with the protein ensure efficient light harvesting in a noisy environment. 82,83 Thus, the protein scaffold seems not only to fix tightly the relative orientations between chromophores in the L1 site, 80 but also to modulate their site energies, to maximise both light-harvesting and photoprotective roles. In this context, carotenoid composition becomes dispensable for the quenching function of LHCII.…”
Section: Papermentioning
confidence: 99%
“…81 The diversity of pigment types and the controlled interactions between them and with the protein ensure efficient light harvesting in a noisy environment. 82,83 Thus, the protein scaffold seems not only to fix tightly the relative orientations between chromophores in the L1 site, 80 but also to modulate their site energies, to maximise both light-harvesting and photoprotective roles. In this context, carotenoid composition becomes dispensable for the quenching function of LHCII.…”
Section: Papermentioning
confidence: 99%
“…Moreover, by a combination of single-molecule and ensemble ultrafast spectroscopy, we were able to observe how the protein motion causes the energetic disorder in individual LH2 complexes. We have found that the LH2 antenna is constructed in such a way that the excitation remains delocalized in the presence of the protein fluctuations [33 ]. This results in a robust, energetically stable and fast energy-transferring state.…”
Section: Light-harvesting Complex 2 Of Purple Bacteriamentioning
confidence: 96%
“…Results of 2D-ES suggest an intimate role of the environment in the form of molecular vibrations on quantum coherent energy and electron transfer processes. This environment changes from complex to complex as well as on relatively slow time scales (milliseconds to minutes), as suggested by the distinct, time-varying energy transfer pathways reported in studies on single light-harvesting complexes [11,[60][61][62]. Owing to this heterogeneity, generally termed 'static disorder', which originates from relatively slow protein conformational dynamic fluctuations, the decay of oscillations of spectral features is strongly affected by ensemble averaging.…”
Section: Single Molecule Spectroscopymentioning
confidence: 99%